Peningkatan Budaya Literasi Melalui Program Pojok Baca Siswa Sekolah Dasar - Tsani Shofiah Nurazizah; Yona Wahyuningsih (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This research was conducted based on the low literacy culture of reading and some grade 2 students who still have difficulty reading. One of the school literacy movement programs that can be done to increase students' interest in reading is the reading corner program. The purpose of this study was to determine the role of the reading corner in students' interest in reading. The type of research used in this research is descriptive-qualitative, with research methods in the form of observation and literature study. The research subjects were grade 2 students at SDN Tirtayasa. The object of this research was the reading corner in Grade 2. The results showed that the reading corner played a very important role in growing and increasing students' interest in reading at school. Based on the research, it can be concluded that with a reading corner, students can use the reading corner as the closest reading facility, as the closest reading material, and also as a comfortable and attractive place to increase reading interest. The reading corner is managed by teachers as well as students, with the aim of introducing students to fun learning resources